Investigating Elastic Deformation of Ordered Precipitates by Ab Initio-Informed Phase-Field Crystal Modeling - Jacob Holmberg-Kasa; Pär A. T. Olsson; Martin Fisk (Metals)
Ni-based superalloys, essential for high-temperature applications, derive strength from coherent second-order precipitates that impede dislocation motion through coherency misfit and elastic mismatch. This study employs multi-component phase-field crystal (PFC) simulations to explore the elastic deformation of such precipitates. Using a binary ordered square structure for the precipitate and a single species square structure for the matrix, elastic properties and lattice parameters are fitted to data from ab initio density functional theory calculations for Ni and Ni3Ti systems. Simulations reveal a smooth strain gradient across the matrix–precipitate interface with coherency misfit influenced by precipitate size and strain state. These findings highlight the utility of PFC simulations for understanding strain distribution and deformation in precipitate–matrix systems with the potential to offer insights for both experimental and computational studies.